A Case of Odontogenic Orbital Cellulitis Causing Blindness: A Case Report - Vimlesh Sharma; Laltanpuia Chhangte; Vijay Joshi; Swati Gupta; Kalpana (Delhi Journal of Ophthalmology)
Aim: To report a case of odontogenic orbital cellulitis causing blindness in young male Methods: We report a rare case of odontogenic orbital cellulitis secondary to periodontal abscess, due to which a young male lost his sight. Results: After extensive clinical examination and investigations diagnosis of odontogenic orbital cellulitis. Patient took incomplete treatment and showed negligence while taking treatment for recurrent periodontal abscess. As a result he developed orbital cellulitis and temporal fossa abscess, which ultimately caused blindness in his right eye. Discussion: Orbital Cellulitis is the infection of the soft tissues behind the orbital septum. Orbital cellulitis is a life threatening infection. It is an ocular emergency that not only threatens vision but also can lead to life-threatening complications such as cavernous sinus thrombosis, meningitis, and brain abscess. The major causes of orbital cellulitis are sinusitis (58%), lid or face infection (28%), foreign body (11%), and hematogenous (4%), odontogenic 2-5%. Odontogenic i.e tooth related causes of orbital cellulitis are very less.